vol. 1 - Baluyot, Ben (Philippines)
The lessons presented in this module are very basic. You need not add to them. The reason is to make them simple enough to understand and remember. They are like the basic chords you learn in playing musical instruments. Once you have learned these basic chords you can play almost any piece of musical composition. Another reason is easy to transfer. You can easily teach these lessons to your new converts who will also teach others.
Keywords: Reaching the nations